Selection of Improved Native Avocado Varieties in Southern Nuevo León, Mexico - Genoveva, Alvarez Ojeda María; Díaz, Efraín Acosta; Guerra, Raúl Rodríguez; Ramírez, José Saúl Padilla; León, Isidro Humberto Almeyda (European Journal of Applied Sciences, 2025)
Given the importance of avocado cultivation in Mexico, several studies have been conducted to understand and evaluate the genetic and morphological variability, as well as the total oil content and fatty acid profile of different genotypes, particularly of native avocados from various regions of the country. Recently, a group of outstanding materials were identified as potential bud donors, and one variety was selected as a possible rootstock in the state of Nuevo León. Based on this, the objective of this study was to select the most outstanding improved native avocado varieties based on the phenological, morphological, and chemical characteristics of the fruit. A group of 10 outstanding genotypes was used, derived from an initial batch of 29 materials collected in the southern region of the state of Nuevo León. A commercial “Hass” variety was also included. Six ripe fruits were sampled from each variety and evaluated, and their phenological, morphological, and chemical characteristics were determined. Based on the results, the improved native varieties María Elena, Plátano Grueso, Mantequilla, and Calabo were selected, given that they exhibited outstanding phenological, morphological, and chemical characteristics. These varieties represent a viable alternative for the sustainable and phased production of native avocados through an organized orchard planting system in the southern region of the state of Nuevo León.